Toxicopathological changes of ciprofloxacin in broiler chickens - NIYOGI, D; BHOWMIK, M K (The Indian Journal of Animal Sciences, 2014)
Toxicopathological changes of graded dose levels of ciprofloxacin, a second generation of quinolone chemotherapeutic agent. were determined in broiler chickens. Birds orally administered with therapeutic dose (5mg kg-4 b/wt) developed mild gastrointestinal signs, anaemia, leucopoenia, hypoglycemia, hypoproteinemia, increased transaminase activity and low degree of toxic hepatitis and nephrosis. Double and triple therapeutic doses produced severe gastrointestinal signs. partial loss of body weight and leg weakness accumpanied with significant (P